High Grade Appendiceal Mucinous Neoplasma Reviewing Primary Tube Malignancy : A Case Report - Kurnia, Irfan; Antonius, Puja Agung; Muhammad, Syammel (Fakultas Kedokteran Universitas Andalas, 2023)
Appendiceal mucinous neoplasms (AMNs) are rare tumors accounting for less than 1% of all cancers. The clinical presentations of AMN vary significantly and the diagnosis of most patients is during surgery for suspected appendicitis, peritonitis or gynecological cancer. There were many case reports AMN mimicking an ovarian cancer. In this case, we reported a 64-year postmenopause woman with diagnosed peritonum carcinomatosis dd/ ovarian cancer and it actually AMN in RSUP dr. M. Djamil Padang, West Sumatera. The diagnosis is estimated by ultrasonography (USG), computed tomography (CT), magnetic resonance imaging (MRI) and diagnostic laparoscopy followed by histopathologic verification. The evaluation of the prognosis of appendix mucinous adenocarcinoma mainly depends on whether the tumour is in an advanced stage, the degree of malignancy, and whether an AMN is formed